Analiza učinkovitosti igre v napadu slovenske košarkarske reprezentance v skupinskem delu evropskega prvenstva leta 2017 - Horvat, Patrik (Šport (Ljubljana), 2018)
Using a sample of five matches played during the group stage of the 2017 European Basketball Championship, we analysed the efficiency of offences by the Slovenian National Basketball Team which won first place at the championship and became the European Champion. Using the official video-recordings from FIBA's website, we watched and analysed all offences and classified them as fast breaks, early offences and set offences. The following characteristics were identified for each of the abovementioned types: offence duration, number of players directly involved in offence, type of offence completion, (un)successfulness of the offence and the player who completed the offence. The analysis of efficiency revealed that the Slovenian game was based on fast breaks and fast completion of early and set offences as well as that the "long bench" with many rotations helped maintain the high pace of the game throughout the group stage of the competition.
Keywords: analiza igre; člani; evropsko prvenstvo; košarka; šport; učinkovitost